Mechanochemical synthesis of chemically stable isoreticular covalent organic frameworks - Biswal, Bishnu P.; Chandra, Suman; Kandambeth, Sharath; Lukose, Binit; Heine, Thomas; Banerjeet, Rahul (Journal of the American Chemical Society, 2013)
Three thermally and chemically stable isoreticular covalent organic frameworks (COFs) were synthesized via room-temperature solvent-free mechanochemical grinding. These COFs were successfully compared with their solvothermally synthesized counterparts in all aspects. These solvent-free mechanochemically synthesized COFs have moderate crystallinity with remarkable stability in boiling water, acid (9 N HCl), and base [TpBD (MC) in 3 N NaOH and TpPa-2 (MC) in 9 N NaOH]. Exfoliation of COF layers was simultaneously observed with COF formation during mechanochemical synthesis. The structures thus obtained seemed to have a graphene-like layered morphology (exfoliated layers), unlike the parent COFs synthesized solvothermally.

Mechanosynthesis of imine, beta-ketoenamine, and hydrogen-bonded imine-linked covalent organic frameworks using liquid-assisted grinding - Das, Gobinda; Shinde, Digambar Balaji; Kandambeth, Sharath; Biswal, Bishnu P.; Banerjee, Rahul (Chemical Communications, 2014)
A variety of aromatic amines/hydrazides and aldehydes have been utilized for the construction of crystalline COFs at a faster rate and in high yield, irrespective of their reactivity and solubility using the Liquid-Assisted Grinding (LAG) method.

Multifunctional and robust covalent organic framework-nanoparticle hybrids - Pachfule, Pradip; Panda, Manas K.; Kandambeth, Sharath; Shivaprasad, S. M.; Diaz, David Diaz; Banerjee, Rahul (Journal of Materials Chemistry A, 2014)
Highly dispersed Pd(0) nanoparticles were successfully immobilized into a stable, crystalline and porous covalent organic framework (COF), TpPa-1, by a solution infiltration method using NABH(4) as a reducing agent. High resolution and dark field TEM images confirmed the uniform loading of the Pd(0) nanoparticles into the TpPa-1 matrix without aggregation. This hybrid material exhibited excellent catalytic activity towards the Cu free Sonogashira, Heck and sequential one pot Heck-Sonogashira cross-coupling reactions under basic conditions, and with superior performance compared to commercially available Pd supported on activated charcoal (i.e., 1, 5 and 10 wt%). Additionally, the precursor Pd(II)-doped COF also displayed competitive catalytic activity for the intramolecular oxidative biaryl synthesis under acidic conditions. Both catalysts were found to be highly stable under the reaction conditions showing negligible metal leaching, non-sintering behavior, and good recyclability. To the best of our knowledge, the organic support used in this work, TpPa-1, constitutes the first COF matrix that can hold both Pd(0) nanoparticles and Pd(II) complex without aggregation for catalytic purposes under both highly acidic and basic conditions.

Mechanochemically synthesized covalent organic framework as a proton-conducting solid electrolyte - Shinde, Digambar Balaji; Aiyappa, Harshitha Barike; Bhadra, Mohitosh; Biswal, Bishnu P.; Wadge, Pritish; Kandambeth, Sharath; Garai, Bikash; Kundu, Tanay; Kurungot, Sreekumar; Banerjee, Rahul (Journal of Materials Chemistry A, 2016)
Mechanochemistry has become an increasingly important synthetic tool for a waste-free environment. However, the poor quality of the so-derived materials in terms of their crystallinity and porosity has been their major drawback for any practical applications. In this report, we have for the first time successfully leveraged such characteristics to show that the mechanochemically synthesized bipyridine based covalent organic framework (COF) outperforms its conventional solvothermal counterpart as an efficient solid-state electrolyte in PEM fuel cells. Marking the first such attempt in COFs, a Membrane Electrode Assembly (MEA) fabricated using the mechanochemically synthesized COF was observed to inhibit the fuel crossover and build up a stable Open Circuit Voltage (OCV = 0.93 V at 50 degrees C), thereby establishing itself as an effective solid electrolyte material (with a proton conductivity of 1.4 x 10(-2) S cm(-1)), while the solvothermally synthesized COF proved ineffective under similar conditions.